2023
DOI: 10.1002/hep.32775
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell transcriptomics uncovers cellular architecture and developmental trajectories in hepatoblastoma

Abstract: Background and Aims: Hepatoblastoma (HB) is the predominant type of childhood liver cancer. Treatment options for the clinically advanced HB remain limited. We aimed to dissect the cellular and molecular basis underlying HB oncogenesis and heterogeneity at the single‐cell level, which could facilitate a better understanding of HB at both the biological and clinical levels. Approach and Results: Single‐cell transcriptome profiling of tumor and paired distal liver tissue samples from five patients with HB was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
6
10
0
Order By: Relevance
“…These findings suggest that EZH2 operates in a predominantly noncanonical manner because canonical EZH2 interacts with and requires EED and SUZ12 16 . The stoichiometry of the PRC2 complex requires correspondingly elevated protein levels of EED and SUZ12 53,54 . Noncanonical mechanisms of EZH2 function as they relate to β‐catenin function have been reported.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…These findings suggest that EZH2 operates in a predominantly noncanonical manner because canonical EZH2 interacts with and requires EED and SUZ12 16 . The stoichiometry of the PRC2 complex requires correspondingly elevated protein levels of EED and SUZ12 53,54 . Noncanonical mechanisms of EZH2 function as they relate to β‐catenin function have been reported.…”
Section: Discussionmentioning
confidence: 90%
“…16 The stoichiometry of the PRC2 complex requires correspondingly elevated protein levels of EED and SUZ12. 53,54 Noncanonical mechanisms of EZH2 function as they relate to β-catenin function have been reported. A recent study demonstrated that EZH2…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During post-hepatectomy acute liver injury, newborn hepatocytes arise from the self-replication of residual hepatocytes, highlighting the proliferation and division of mature hepatocytes as the fastest and most effective method of liver regeneration (Michalopoulos and Bhushan 2021). Notably, Single-cell RNA sequencing (scRNA-seq) is a powerful approach to explore cell structure and characterize cell identity (Huang et al 2022), especially identifying different cell populations and explaining the heterogeneity or correlation between cells. In conclusion, liver regeneration is a critical topic of interest in clinical scenarios and cutting-edge cellular therapies for liver disease.…”
Section: Introductionmentioning
confidence: 99%